Wildemania — przekład Salomé Oscara Wilde’a a literatura chorwacka na początku XX wieku - Medić, Igor (Przekłady Literatur Słowiańskich, 2021)
The Irish writer Oscar Wilde was extremely popular in Croatian culture in the first decades of the 20th century. Although Croatian writers of that time generally did not read the original works of British authors but rather their translations, Wilde’s popularity in Germany and Vienna sparked interest in his works among the Croatian readership and spectatorship. This paper explores the translation of Wilde’s Salomé from German by Julije Benešić and Nikola Andrić, and the complex influence that this translation had on Croatian literature of early modernism, relying primarily on the interpretation of the same motif in the texts of young Fran Galović and Miroslav Krleža. The paper argues that the influence of Wilde’s aestheticism is visible not only in the adoption of typical motifs, characters, or atmosphere but also in the autonomous and self-reflective language play in Krleža’s texts.